PERILAKU KEUANGAN GENERASI Z PENGGUNA M-BANKING BCA DI SURABAYA: PENGARUH LITERASI KEUANGAN, GAYA HIDUP, LOCUS OF CONTROL, DAN FINTECH SEBAGAI MODERASI - Naufal Afif Dwinka Tantra; Nurjanti Takarini (MANAJEMEN DEWANTARA, 2025)
The rapid growth of financial technology has made financial activities more practical yet it has also heightened the risk of consumptive behavior among Generation Z due to limited financial literacy and self-control. 147 Generation Z BCA Mobile customers in Surabaya provided primary data for this study, which uses a quantitative methodology. Purposive sampling was used to choose respondents based on predetermined standards. The Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to analyze the data. The findings show the benefical impact of financial literacy and locus of control, while lifestyle has a considerable detrimental impact on financial behavior. Furthermore, financial technology amplifies the influence of locus of control on financial behavior, diminishes the impact of financial literacy, and is unable to mitigate the influence of lifestyle on financial conduct